The Improvement Conservation Model of Germ Plasm Sahiwal Cross Cattle Although Agribusiness Approach in South East Sulawesi Province - Indonesia - Wayan Sura,; La panga,; Fara Sasmita,; Ayu Lestari Dewi, (International Journal of Management and Education in Human Development, 2022)
This study aims to (1) deliver the right adaptation model of cross-legalized Sahiwal cow germplasm, its dual purpose as a producer of beef and milk in Southeast Sulawesi (2) Prevent the extinction of Sahiwal Cross Cattle in Southeast Sulawesi, and (3) Improve the genetic quality of Sahiwal Cross Cows the community through Artificial Insemination (IB) technology uses FH cement to increase production and productivity. This research was carried out in Southeast Sulawesi Province from April to August 2018. This research was a Survey study, meaning that research described certain objects describing the Study of Sahiwal Cattle Germplasm Adaptation Model Cross Dual Purpose Cattle Producing Meat and Milk. This research is classified into a qualitative descriptive research group, namely the search for facts with the right interpretation in order to determine the development of Sahiwal Cross cattle both in terms of increasing population and genetic quality. The data analysis technique used in this study was qualitative descriptive analysis. The results showed that: (1) Protection and preservation of Sahiwal Cross Cattle germplasm is one alternative to increase population and improve the productivity of Sahiwal Cross Cattle in Southeast Sulawesi; (2) The development of cross-validated cattle adaptive is still widely found in Konda Subdistrict Konawe Selatan District when compared to Bombana, Konawe and Kolaka Regencies (3) The right adaptation model to protect and preserve living cross-Sahiwal cattle germplasm is In-Situ Conservation / In-situ prescriptions, namely limiting strict crossing with local cows and maximizing the implementation of applied technology of Artificial Insemination (IB) for crossing two legitimate Sahiwal cattle with two FH cattle so that the Sahiwal cross cattle are expected can have 75% of milk Cow type with Blood Resilience’s Indexes.